Targeting RIPK1 kinase for modulating inflammation in human diseases - Li, Wanjin; Yuan, Junying (Frontiers in Immunology, 2023)
Receptor-Interacting Serine/Threonine-Protein Kinase 1 (RIPK1) is a master regulator of TNFR1 signaling in controlling cell death and survival. While the scaffold of RIPK1 participates in the canonical NF-κB pathway, the activation of RIPK1 kinase promotes not only necroptosis and apoptosis, but also inflammation by mediating the transcriptional induction of inflammatory cytokines. The nuclear translocation of activated RIPK1 has been shown to interact BAF-complex to promote chromatin remodeling and transcription. This review will highlight the proinflammatory role of RIPK1 kinase with focus on human neurodegenerative diseases. We will discuss the possibility of targeting RIPK1 kinase for the treatment of inflammatory pathology in human diseases.